2016
DOI: 10.1038/srep24540
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance is associated with altered amino acid metabolism and adipose tissue dysfunction in normoglycemic women

Abstract: Insulin resistance is associated adiposity, but the mechanisms are not fully understood. In this study, we aimed to identify early metabolic alterations associated with insulin resistance in normoglycemic women with varying degree of adiposity. One-hundred and ten young and middle-aged women were divided into low and high IR groups based on their median HOMA-IR (0.9 ± 0.4 vs. 2.8 ± 1.2). Body composition was assessed using DXA, skeletal muscle and liver fat by proton magnetic resonance spectroscopy, serum meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
48
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 55 publications
10
48
1
Order By: Relevance
“…These findings may explain in part our previous finding that, among participants of PREDIMED who were initially free of diabetes, the MedDiet+EVOO intervention significantly reduced risk of type 2 diabetes [16]. Our results are consistent with the findings from our systematic review on metabolomics and type 2 diabetes [6], other recent findings [5, 712, 25] and our previous observation on the association between plasma levels of BCAA and incident cardiovascular disease [26]. …”
Section: Discussionsupporting
confidence: 92%
“…These findings may explain in part our previous finding that, among participants of PREDIMED who were initially free of diabetes, the MedDiet+EVOO intervention significantly reduced risk of type 2 diabetes [16]. Our results are consistent with the findings from our systematic review on metabolomics and type 2 diabetes [6], other recent findings [5, 712, 25] and our previous observation on the association between plasma levels of BCAA and incident cardiovascular disease [26]. …”
Section: Discussionsupporting
confidence: 92%
“…In MSUD patients, high BCAA blood concentrations cause neurological damage associated with sustained inflammation including elevated serum levels of IL‐1β, IL‐6 and IFN‐γ 34. In normoglycemic women, insulin resistance was associated with increased serum BCAA concentrations, down‐regulation of mitochondrial energy metabolism and increased expression of inflammation‐related genes (CCL2‐CCL5) in the adipose tissue 35. Finally, our recent study demonstrated that elevated concentrations of BCAA induced inflammation and oxidative stress in PBMC 22.…”
Section: Discussionmentioning
confidence: 99%
“…Phenylalanine and tyrosine are closely associated with each other and glutamate is associated with the above two AAAs through ammonia. Some studies have suggested that amino acids adjust insulin sensitivity through gluconeogenesis, especially impaired insulin sensitivity related to dysfunction of amino acid metabolism, and it may result in adiposity or diabetes [29,30]. Amino acids could modulate peripheral insulin sensitivity and eventually contribute to T2DM patients with insulin resistance [31].…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacometabolomics could provide certain advantages compared to other "omics" fields because metabolites that intermediates and end products in metabolic pathway necessary to reflect better physiological dysfunctions, drug response and enable to diagnosis using biological fluids [25,[29][30][31][32][33][34][35][36][37][38]. A previous study reported the integration of metabolite levels of bio fluids and other biochemical information (e.g., glucose and HbA1c) could better reflect T2DM risk than a single established risk factor [29,[39][40][41][42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%